About the Need of a New Look at Safety as a Goal and Constraint in Air Traffic Management. (2017) - Skorupski, Jacek
Abstract: In the traditional approach to Air Traffic Management, safety is treated as a main goal. Current safety management systems are constructed according to this approach. However, with the development of technical support systems, further increasing the real level of safety is difficult for operational, technical and economic reasons. We should therefore expect that in future safety will be treated as a constraint in the process of transport systems optimization instead of a goal. The paper proposes to use the cost, the air traffic smoothness or the environmental nuisance as new criteria for characterizing the quality of air traffic. This requires both new measures of the criteria proposed and a new generation of safety performance indicators allowing quantitative comparison of the level of safety for different organizational variants of the transport system. This paper presents an analysis of the problem and the proposal for such indicators. The essence of this concept is the hierarchical combination of indicators of a very general nature with specific and specialized ones.